Economic inequality breeds corrupt behaviour. (29th November 2022) - Wei, Cong; Dang, Jianning; Liu, Li; Li, Chao; Tan, Xuyun; Gu, Zibei
Abstract: Economists and political scientists have long debated the relations between economic inequality and corruption at the societal level. Extending this literature, we proposed and tested that economic inequality breeds the corrupt behaviour of individuals. Analyses of 45‐year archival data from the United States found that official corruption crimes were more prevalent in years and states with greater economic inequality. Three subsequent experiments ( N =  776) using economic games showed that individuals exposed to greater economic inequality exhibited more corrupt behaviour in both Chinese and American cultures. Furthermore, the increased desire for wealth and the perception of reduced fairness accounted for this effect. These findings highlight that excessive economic inequality creates a competitive environment in which people give priority to themselves over others and suggest a vicious cycle between economic inequality and corruption.